Analysis of the Effectiveness of Digital Marketing Strategies In Increasing New Student Admissions - Saputra, Ade; Sahadah, Dewi Nelly; Solaiman, Deny; winanti, winanti; Goestjahjanti, Francisca Sestri; Yulia, Yayah; Supriyanto, Supriyanto; Tiara, Beby; Nurasiah, Nurasiah; Basuki, Sucipto; eka , Henry antonius; Pebrina, Erni Taruli (International Journal of Innovation Research in Education, Technology and Management, 2025)
The ever-evolving digital era, digital marketing strategies are key for educational institutions, including Vocational School, to increase new student enrollment. This research aims to analyze the extent to which the digital marketing strategy implemented by Vocational School is effective in attracting prospective students and their parents. The results of the study are expected to provide in-depth insights into the success of existing digital marketing strategies, as well as recommend improvements and new tactics that can increase the enrollment of new students at Vocational School. By understanding the effectiveness of digital marketing strategies, Vocational School can optimize their marketing efforts, expand their reach, and ensure sustainable growth in a competitive education environment.